The influence of negative selection on stature in population - an ecological approach - Jurynec, Roman (Anthropological Review, 1986)
This work was based on material of military anthropological survey of Poland, which was carried out in the years 1921-1923 under the leadership of J. Mydlarski. Subject of investigation were data concerning 2569 soldiers born in the years 1899-1901 in Poznań province and the southern part of Pomeranian province. The purpose of this work was to evaluate the dependence between the environmental conditions and the mean body height in the population. The results are analysed in the light of the hypothesis about a selective character of the environmental influence on the population. In agreement with the accepted assumption, the mean body height in the population is influenced in a contrasting way by two partially different environmental factors: ’living conditions’ understood as the level of satisfying the basic life needs of the individual, and ’selective pressure’ being the sum of life dangers. These factors act on the individuals in a differentiated way depending on the genetic predispositions conditioning their adaptation ability, resistance and general health. The selective pressure through negative selection (differential mortality) eliminating from the population individuals who in the given living conditions develop and realize their growth potential in the poorest way limits the negative influence of living conditions on the mean body height in the population. This selection can have both a directional and stabilizing character. The mean body height of mature individuals in the population depends on the living conditions in which their development took place and on the selection degree by differential mortality. For the evaluation of the living and environmental conditions data were utilized concerning the number of children born, living and deceased in the families from which the investigated subjects originated. On this basis the environmental conditions were evaluated both in families and in the socio-professional groups distinguished on the basis of the father’s profession and the birth place ("village", "town"). In case of families, the evaluation was based on the assumption that the number of children in the family is a burdening factor, and the morality is in a great degree the effect of worse living and environmental conditions. Better environmental conditions in socio-professional groups are testified primarily by a lower percentage of deceased children in the families from which the investigated subjects belonging to the given group originate, as well as by a greater number of children. The departing point of the hypothesis accepted at the outset was the fact that in the material no definite dependence was found between the evaluated living and environmental conditions and the mean body height. The analysis of families has shown that on the average the tallest were the subjects originating from families which due to the number of living children in the family and the percentage of the deceased ones could provide the average living and environmental conditions (Tables 8 and 11). Worse environmental conditions, in case of socio-professional groups, caused by mortality and fecundity in the families from which the subjects belonging to the definite groups originated were not always connected with smaller body heights (Tables 9 and 10).